Sequence Analysis of the Hypervariable Region in hmtp210 of Avibacterium Paragallinarum - Araya, Edward (2017)
The hmtp210 gene of Avibacterium paragallinarum, the causative agent of infectious coryza, encodes an outer-membrane hemagglutinin (HA) that plays an essential role in pathogenicity. A hypervariable region within this HA, which is highly antigenic, is proposed as a candidate for recombinant vaccine production. Nonetheless, little is known about its genetic variability. We performed sequencing analysis of the hmtp210 hypervariable region in 16 clinical isolates from Costa Rica and compared them with 4 vaccine strains and the hmtp210 sequences available in public databases. Except for isolate ApCR12, all isolates showed high identity with reference vaccine strains 0083 and H18. Better genetic characterization of the hypervariable region of hmtp210 is necessary to develop better immunogenic strategies and improved molecular typing methods.